Hubungan Literasi Kesehatan Dengan Perilaku Hidup Bersih Dan Sehat Rumah Tangga di Wilayah Kerja Puskesmas I Tabanan, Bali - Putu Ika Farmani; Putu Ayu Laksmini (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: Health literacy is the knowledge, motivation, and competence used to understand, assess, and use information to decide about health, including Healthy and Clean-Living Behaviour among household. The Healthy and Clean-Living Behaviour among household is the effort of family empower to know, wants, and could be practice in community. This study aims to determine the relationship of health literacy and Healthy and Clean-Living Behaviour among households in the Area of PHC I Tabanan.Methods: The cross-sectional analytic design study was conducted to collect data by interview using The HLS-EU-Q16 and Healthy and Clean-Living Behaviourâ€™s questionaire. Sample was 200 families in the area of PHC I Tabanan that chosed by cluster random sampling. The variable researchâ€™s was socio demographic, health literacy, and Healthy and Clean-Living Behaviour. Data was analysed descreptively and analytic using Gamma test.Results: Research result show socio demographic of responden were female (63%), age average 48 y.o, married (90.5%), history of education was senior high school (49%), and 53.5% was enterpreuner. 51.5% Respondent with high level of health literacy and 84.5% respondent withÂ level of Healthy and Clean-Living Behaviour with